The Role of the PAI Teacher in Implementing the Values of Inter-Religious Tolerance in Students - Imam Tabroni; Diki Muhammad Abdillah; Siti Nurjanah; Syarah Fakhrunnisa (Jurnal Multidisiplin Madani, 2022)
Indonesia is a pluralistic country that has a variety of ethnic groups, cultures, and religions that differ from one another. These differences, especially religious differences, are of course very risky to trigger disputes if the harmony cannot be maintained by each group. Therefore, a figure is needed who is expected to be able to maintain the stability of tolerance that is built between these groups. One of them is a teacher. A teacher, especially an Islamic education teacher, has a big enough contribution to be able to build tolerance that exists in every individual in this country. In this paper, the author tries to express the important roles that PAI teachers have in instilling an attitude of tolerance for religious diversity. This study uses the Library Research method in which researchers obtain data by studying and recording books, archives or documents, and matters related to research . After conducting the research, the authors conclude that PAI teachers have three important roles in instilling tolerance between religious communities in their students, namely; 1) The teacher organizes students in respecting fellow students and is accustomed to respecting when someone speaks in class, 2) The teacher instills the value of tolerance with an attitude of mutual cooperation in helping between school members and religious activities regardless of inter-religious background, and 3) To instill religious tolerance, PAI teachers must be supported by the principal and a conducive environment and there must also be adequate facilities.